Doing the right thing : a six-part exploration of ethics - Colson, Charles W.; George, Robert; Hume, Brit. ([Ashburn, VA] : BreakPoint Inc., 2011)
Doing the Right Thing explores the ethical and moral breakdown that is assaulting culture from all sides. Through panel discussions, interviews, and student questions, this video study hosted by Brit Hume raises ethical issues in a compelling and fresh way, stimulating thought, discussion, and action. The six DVD sessions and accompanying study guide encourage participants to examine themselves and how ethical and character issues relate to their lives at home, school, and the workplace.
Disc 1 : how did we get into this mess? -- Disc 2 : is there truth, a moral law we can all know? -- Disc 3 : if we know what is right, can we do it? -- Disc 4 : what does it mean to be human? -- Disc 5 : ethics in the market place -- Disc 6 : ethics in public life.
Includes a leader's guide.
Produced by BreakPoint Inc.
Moderated by Brit Hume
Hosted by Chuck Colson & Robert George
Closed-captioned
Keywords: Ethics; Vido recording for the hearing impaired